Unveiling Gender Disparities in Legal Traditions: A Study of Deferred Mahar within Customary Law - Ilmiati, Ilmiati; Nazhifah, Lazimatun; Iqbal, Muhammad; Makkarateng, Ma'adul Yaqien; Arake, Lukman (De Jure: Jurnal Hukum dan Syari'ah, 2025)
In the framework of Indonesia's legal pluralism, the deferred mahar tradition leads to societal disputes, raises divorce rates, and encourages debt-related crimes by placing financial burdens on the groom’s side. Such systemic issues critically need policy reforms. This paper primarily aims to critically analyse this phenomenon—the mowindahako tradition—within the legal plurality system observed by the Tolaki ethnic community in Southeast Sulawesi, Indonesia. Data was gathered through observation and in-depth interviews and subsequently analysed within the theoretical framework of Living Customary Law (LCL). The findings suggest that the practice of deferred mahar in Indonesia can be attributed to the complex interplay between customary law, the state, and religion within the country's framework of legal pluralism. Both legal politics and gender biases influence this phenomenon, evident in traditional institutions' policies that empower women to dictate substantial dowry sums, thereby imposing a financial burden on men. Concurrently, customary institutions provide men with credit to help them pay dowries, thereby enhancing their convenience. This approach has led to prolonged societal disputes, reflected in increased divorce rates and rising criminal prosecutions due to debt-related issues. This paper provides a comprehensive analysis of the Deferred Mahar policy implemented by the Tolaki tribal customary institution.